2017
DOI: 10.1186/s11671-017-1893-3
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effects of Dimorfolido-N-Trichloroacetylphosphorylamide and Dimorfolido-N-Benzoylphosphorylamide in Combination with C60 Fullerene on Leukemic Cells and Docking Study of Their Interaction with DNA

Abstract: Dimorfolido-N-trichloroacetylphosphorylamide (HL1) and dimorfolido-N-benzoylphosphorylamide (HL2) as representatives of carbacylamidophosphates were synthesized and identified by the methods of IR, 1H, and 31P NMR spectroscopy. In vitro HL1 and HL2 at 1 mM concentration caused cell specific and time-dependent decrease of leukemic cell viability. Compounds caused the similar gradual decrease of Jurkat cells viability at 72 h (by 35%). HL1 had earlier and more profound toxic effect as compared to HL2 regardless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…However, if applied in doses less than 10–20 µg/mL (depending on cell line) C 60 fullerene didn’t increase the number of apoptotic and pre-apoptotic cells [ 46 ], being, therefore, relatively low-toxic. Low cytotoxicity of C 60 fullerene against normal and neoplastic cells was also demonstrated in [ 13 , 47 ]. Thus, C 60 fullerene did not affect leukemic cell viability when applying at 3.6–144 µg/mL (CCRF-CEM, Jurkat, Molt-16 cells), IC 50 for HEK293 cells was equal to 383.4 µg/mL.…”
Section: Discussionmentioning
confidence: 78%
“…However, if applied in doses less than 10–20 µg/mL (depending on cell line) C 60 fullerene didn’t increase the number of apoptotic and pre-apoptotic cells [ 46 ], being, therefore, relatively low-toxic. Low cytotoxicity of C 60 fullerene against normal and neoplastic cells was also demonstrated in [ 13 , 47 ]. Thus, C 60 fullerene did not affect leukemic cell viability when applying at 3.6–144 µg/mL (CCRF-CEM, Jurkat, Molt-16 cells), IC 50 for HEK293 cells was equal to 383.4 µg/mL.…”
Section: Discussionmentioning
confidence: 78%
“…We have used two versions of molecular modeling of HL, C 60 fullerene and DNA interaction, which were proposed in [ 16 ] and proved to be useful for interpretation of MD simulation results. We have used 1XRW PDB structure of DNA molecule in the version, when initially HL and then C 60 molecule intercalate into DNA (HL+C 60 ) and 2MIW PDB structure of DNA molecule - in the version, when initially C 60 molecule and then HL intercalate into DNA(C 60 +HL).…”
Section: Resultsmentioning
confidence: 99%
“…5 ). Recently, we have shown that another CAPh representative dimorfolido-N-trichloracetylphosphorylamid caused 50% decrease of CCRF-CЕM cells viability at 72 h in concentration 1 mM [ 16 ]. The comparative analysis of these data demonstrates that introduction of phenoxy instead of morfolido groups into the structure of CAPh derivative allowed to decrease by two orders its effective toxic concentration against leukemic cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations